Factors Related to Hearing Threshold of Workers at PT. X - Putri, Salsabila Liandra; Afianah, Nuzula (International Journal of Health and Information System, 2023)
Physical hazards are one of the several types of dangers in Occupational Health and Safety. Companies or industries that use machines in their work processes have the potential to cause a physical hazard. One of the physical hazards is noise. Noise exposure can have an impact on employee health, namely hearing loss. A decrease in hearing threshold values can cause communication disorders and concentration problems. Variables of sound intensity, period of work, age, and disease history can influence the reduction in hearing threshold values. The results of a preliminary study on workers at PT. X indicates the sound intensity is above the threshold value, namely 86dB and 16.6% of workers experience hearing loss. The aim of this research is to determine the factors related to the hearing threshold values of workers at PT. X. The methodology in this research uses a cross-sectional approach. This study had 30 workers as samples using total sampling techniques. The results showed that the sound intensity factors (ρ = 0.030) and disease history (ρ = 0.013) were related to the hearing threshold value. Meanwhile, the factors of work experience (ρ = 0.704) and age (ρ = 1.000) are not related to the hearing threshold value. The conclusion of this research is that there is a relationship between sound intensity and history of illness with the hearing threshold value of workers at PT. X.